Seamless Integration of RESTful Services into the Web of Data. (22nd February 2012) - Lanthaler, Markus; Gütl, Christian
Abstract : We live in an era of ever-increasing abundance of data. To cope with the information overload we suffer from every single day, more sophisticated methods are required to access, manipulate, and analyze these humongous amounts of data. By embracing the heterogeneity, which is unavoidable at such a scale, and accepting the fact that the data quality and meaning are fuzzy, more adaptable, flexible, and extensible systems can be built. RESTful services combined with Semantic Web technologies could prove to be a viable path to achieve that. Their combination allows data integration on an unprecedented scale and solves some of the problems Web developers are continuously struggling with. This paper introduces a novel approach to create machine-readable descriptions for RESTful services as a first step towards this ambitious goal. It also shows how these descriptions along with an algorithm to translate SPARQL queries to HTTP requests can be used to integrate RESTful services into a global read-write Web of Data.